PENGARUH KESEHATAN DAN KESELAMATAN KERJA TERHADAP KINERJA KARYAWAN DI BANDARA INTERNASINAL SUPADIO PONTIANAK - Koesmoyowati, Chyndie; Melly A.D, You She (Fakultas Ekonomi dan Bisnis, 2022)
Performance is a process carried out by a group of people in a company to create a product or service. Employees must receive special attention from the company. The fact that humans are the main assets in an organization or company, must get serious attention and be managed as well as possible. This is intended so that the human resources owned by the company are able to provide optimal contributions in the effort to achieve organizational goals. In the management of human resources, management is needed that is able to manage resources in a systematic, planned, and efficient manner. The purpose of this study was to determine the effect of occupational health and safety on the performance of employees at the Pontianak Supadio International Airport. The research method used in this research is associative and quantitative research. population, the population of this research is all employees of Gapura Angkasa International Airport Supadio Pontianak Kalimantan, totaling 36 people. The sampling technique is saturated sampling. The instrument used is a questionnaire. Regression data analysis. There is an effect of work safety (X1) on the performance of Karaywan Gapura Angkasa at Supadio Pontianak International Airport Results There is an effect of occupational health (X2) on the performance of Gapura Angkasa employees at the Pontianak Supadio International Airport. Based on the results of the analysis with simultaneous significance testing (f test) and partial significance test (t test) it can be concluded that Occupational Safety and Health has a positive and significant effect on employee performance, where employee performance can be explained by Occupational Safety and Health of 46, 3%. While the remaining 53.7% is explained by other factors not examined by the researchers in this study.